Conversation Potentials of Haydarpasa Station Roundhouse - Yazar, Nadide Ebru; Binan, Can Sakir (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2019)
Railways are technical systems that has social, political and economical impacts on World history. They are regarded and preserved as instances of endustrial heritage. Conservation of railway studies began in the early 19th century, and passed through various phases. Today, railway conservation studies are expected to 'conserve all scientific and technical skills and include all infrastructures': Railways require periodic maintenance in order to operate and sustain their passenger and freight transportation. In station sites, these functions are fulfilled by operational facilities. Locomotive depots are one of the main buildings of these facilities. Roundhouses represent a distinguished architectural typology among locomotive depots regarding their architectural characteristics, their plans and structural systems. Roundhouses are often become subjects of researches on railway heritage as they are regarded as the symbolic buildings of the steam engine era. In order to regard Turkish railway sites as a whole and define the context of Turkish railway heritage, there is a need to identify such facilities and services and their operational principles. This paper will introduce roundhouses along with their technical and architectural specifications. Then, the roundhouse at Haydarpasa railway site will be considered as a case study to discuss the conservation challenges and potentials of these unique heritage assets.
Keywords: Roundhouse; railway heritage; Haydarpasa Station; conservation; Architecture